2012
DOI: 10.1002/ijc.27706
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GTP cyclohydrolase attenuates tumor growth by reducing angiogenesis and M2‐like polarization of tumor associated macrophages

Abstract: GTP cyclohydrolase (GCH1) is the key-enzyme to produce the essential enzyme cofactor, tetrahydrobiopterin. The byproduct, neopterin is increased in advanced human cancer and used as cancer-biomarker, suggesting that pathologically increased GCH1 activity may promote tumor growth. We found that inhibition or silencing of GCH1 reduced tumor cell proliferation and survival and the tube formation of human umbilical vein endothelial cells, which upon hypoxia increased GCH1 and endothelial NOS expression, the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 51 publications
1
47
1
Order By: Relevance
“…Because AGMO itself is down-regulated by the proinflammatory stimulus IFN-γ/LPS, this may be part of a complex regulatory network. Alterations of the plasma profile observed in tumor-bearing mice upon pharmacological inhibition of tetrahydrobiopterin biosynthesis (24) are compatible with such a proinflammatory mechanism of AGMO/tetrahydrobiopterin. On the other hand, submicromolar amounts of alkylglycerols, the substrates of AGMO, have been reported to act on lymphocytes by increasing IFN-γ and decreasing IL-4 formation (25), thus acting in a proinflammatory way, and their degradation by AGMO would be antiinflammatory.…”
Section: Discussionmentioning
confidence: 83%
“…Because AGMO itself is down-regulated by the proinflammatory stimulus IFN-γ/LPS, this may be part of a complex regulatory network. Alterations of the plasma profile observed in tumor-bearing mice upon pharmacological inhibition of tetrahydrobiopterin biosynthesis (24) are compatible with such a proinflammatory mechanism of AGMO/tetrahydrobiopterin. On the other hand, submicromolar amounts of alkylglycerols, the substrates of AGMO, have been reported to act on lymphocytes by increasing IFN-γ and decreasing IL-4 formation (25), thus acting in a proinflammatory way, and their degradation by AGMO would be antiinflammatory.…”
Section: Discussionmentioning
confidence: 83%
“…Proteasomal degradation of GCH1 is blocked by metformin-induced AMPK activation resulting in the recoupling of eNOS in endothelial cells (40, 41). On the other hand there is a recent report indicating that in some tumors GCH1 expression might actually be increased (42). This study did not, however, evaluate functional consequence such as BH4:BH2 or cGMP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Lp(a) promotes the differentiation of pro-inflammatory, M1-type macrophages, that secrete a set of pro-inflammatory cytokines (e. g. interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor (TNF)-α) and chemokines, like ‘interferon-gamma-induced protein-10’ (IP10, CXCL10) and ‘Regulated on Activation, Normal T‑cell Expressed and Secreted’ (RANTES, CCL5), leading to activation of T‑helper-1 (Th1) cells and natural killer (NK) cells [2225]. The chemokines CXCL10 and RANTES are accompanied with inhibition of angiogenesis, which may affect function of vasa vasorum [25].…”
Section: Function Of Lp(a)mentioning
confidence: 99%